Efektivitas Pelayanan Perijinan Melalui Sistem Informasi Perijinan Online (SIPON) sebagai Upaya Mewujudkan Sistem Informasi Manajemen pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar - Edi Kurniawan, I Putu Agus; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT The Denpasar City One Stop Integrated Licensing and Service Office implements an extension service and re-registers licenses through the Online Licensing Information System (SIPON). This concept is a development of Management Information System that aims to address problems in extension service and re-registers licenses. This research used descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. This research measures the effectiveness of licensing services through the Online Licensing Information System by measuring the effectiveness of services according to Richard M Steers which consists of goals optimizing, system perspectives, and pressure in terms of employee behavior in the organization. The results of research shows that the effectiveness of licensing services through the Online Licensing Information System (SIPON) has not been maximized. Based on three indicators used to see the effectiveness of services that still encounter several obstacles in each indicator. Keywords : Effectiveness of Services, SIPON, Management Information System